Education in Rahmatan Lil 'Alamin Perspective - Dian Iskandar Jaelani (Al-Hayat Al-Istiqomah Foundation, 2017)
Education is believed to be a force and an awareness to make human beings civilized and dignified, which in the Islamic conception of education is aimed at becoming a